Economic and Technical Analysis of a Hybrid Photovoltaic and Fuel Cell System: Optimizing Configuration and Prospects for Green Hydrogen Development in Vietnam - Phuong Truong Le,; Phuong Long Le,; Van Tri Bui ,; Huu Quang Nguyen, (Journal of Technical Education Science, 2025)
This paper presents the results of an economic and technical analysis of a hybrid system photovoltaic and fuel cells, in which the installed capacity of the photovoltaic system is fixed at 1 MW. The study utilizes weather data from NASA to determine the output capacity of the photovoltaic system, thereby evaluating the efficiency of varying the fuel cell capacity, hydrogen storage tank capacity, and load consumption levels (ranging from 600 kW/day to 1000 kW/day). HOMER Pro software was selected as the primary simulation tool, enabling a comprehensive assessment of both economic and technical aspects. The results indicate that the economically optimal configuration is achieved using a PEM fuel cell with a capacity of 120 kW, a hydrogen storage tank with a capacity of 120 kg, combined with a 1 MW photovoltaic system to meet a load demand of 1000 kW/day. The initial investment cost for this optimal configuration is estimated at USD 779,507. The findings not only clarify the economic efficiency of the hybrid solar-fuel cell system but also demonstrate its potential for extensive energy utilization by leveraging excess capacity, promoting the production and use of green hydrogen, and contributing to Vietnam's sustainable development strategy.